The Model of Formation of Professional Competence of Future Software Engineers - Viktor Sedov (Kherson State University, 2016)
The rapid technological development of modern society fundamentally changes processes of production, communication and services. There is a great demand for specialists who are competent in recently emerged industries. Moreover, the gap between scientific invention and its wide distribution and consumption has significantly reduced. Therefore, we face an urgent need for preparation of specialists in higher education that meet the requirements of modern society and labour market. Particularly relevant is the issue of training of future software engineers in the system of master's degree, which is the level of education that trains not only professionals, but also scientists and university teachers. The article presents a developed model of formation of professional competence of future software engineers in the system of master's degree. The model comprises units of training of future software engineers, identifies methodological approaches, a number of general didactic and methodological principles that underpin learning processes in higher education. It describes methods, forms of organization and means that are used in the system of master's degree, and also provides pedagogical conditions of effective implementation of the model. The developed model addresses the issue of individualization, intensification and optimization of studying. While developing the model, special attention was paid to updating the content of education and searching for new organizational forms of training of future software engineers.